Overview of plant-based natural antioxidants and effect of thermal decomposition - Maheshwari, Neha (Kansas State University, 2016)
The popularity of convenience foods and consumer awareness have indirectly increased the demand for novel and naturally occurring compounds that can delay oxidative deterioration and maintain nutritional quality of foods. Natural antioxidants from certain herbs and spices such as rosmarinic acid from rosemary, thymol from oregano, eugenol from clove, curcumin from turmeric are rich in polyphenolic compounds that provide long term oxidative stability as well as offer additional health benefits. High antioxidative capacity of herbs and spices phenolics could potentially substitute synthetic antioxidants such as butylated hydroxytoluene (BHT), butylated hydroxyanisole (BHA), propyl gallate (PG), octyl gallate, and tert-butylated hydroquinone (TBHQ) in the food system. Synthetic antioxidants such as butylated hydroxytoluene (BHT) and butylated hydroxyanisole (BHA) are thermally unstable and decompose at higher temperatures. However, widely used cooking methods such as baking, frying, boiling, and roasting use high thermal temperature that can chemically degrade herbs and spices and diminish their antioxidative capacity, but they have been little studied. In this context, this review deals with the need of natural antioxidants, spices and herbs as natural antioxidants, their origin, chemical composition, pharmacological, and antioxidant properties. Moreover, the impact of temperature on total antioxidant capacity (TAC) of various herbs and spices such as cinnamon, clove, nutmeg, mace, oregano, rosemary, sage, and turmeric is highlighted. Different antioxidant assays are also studied and this approach revealed that there is a clear correlation between total phenolic content (TPC) and TAC of herbs and spices and specific phenolic compounds are responsible for the antioxidative capacity of particular herb and spice. These findings identified the optimum cooking temperature-time combination which results in the highest retention of antioxidative capacity and assures higher quality of food for the maintenance of human health.
Keywords: Natural antioxidants; Antioxidant activity; Heat treatment; Herbs and spices; Maillard reaction products; Thermal decomposition; Chemistry (0485); Food Science (0359); Nutrition (0570)